Analisis Kelayakan Perubahan fungsi Terminal Penumpang menjadi Fasilitas Parkir Angkutan Barang (Studi Kasus Terminal Terboyo Semarang) - Basuki, Kami Hari; Kushardjoko, Wahyudi; Janita, Andreana; Pratama, Ganis Satria (Department of Civil Engineering, Diponegoro University, 2017)
Semarang City has public transport terminal at Terboyo. It is unperformance terminal has caused by land subsidden and flood. The aims of this study is determined fisibility of Terboyo freight-transport terminal park at Semarang City. Methodology analysis at this study is improved transport modelling to determine freight-transport demand. Traffic counting survey with Manual Kapasitas Jalan Indonesia (MKJI) 1997 method are used to know the road and intersection performances that closest to Terminal Terboyo. The study results have showed most trucks parked in Kaligawe road and Yos Sudarso road was continuous journey, while trucks parked in Ronggowarsito road was a truck with the origin or destination of Semarang. Potential park fasilities at Terboyo is indicated by the length of the vehicle configuration plan of 8 meters and parking 45° obtained as much as 73 PSU (Parkign Space Unit), while the north side of the field with a length of 18 meters and plan vehicle parking configuration 30° obtained 76 PSU. It has powerfull to accommodate parking of heavy vehicles. This studi has not identified the potential of regional freight-transport. Occutionally, the pattern of movement of freight transport does not occur in the local area only. So, that further studies need to be conducted with respect to the coverage area of study on a regional basis.